Determination of the saline water intrusion zone and its contamination with ground water in the Dibddiba aquifer using vertical electrical sounding technique at Basrah Governorate, southern Iraq - Al-Musawi, W.M.; Khorshid, S.Z. (Mesopotamian Journal of Marine Sciences, 2022)
Thirty Vertical Electrical Sounding (VES) measuring points (Schlumberger array) were carried out in order to determine the number of the underlying layers, depths and their thicknesses, as well as ground water table and its influence by the saline water coming from the sea or even underlying layer. These points were distributed within five profiles, 500 m spacing between points. The length of each profile is 3 km and the distance between profiles is 2 km. These points were chosen at Basrah Governorate, southern Al-Zubair district. Qualitative interpretation was applied to study the type of the electrical field curves, which were classified to HKQQ, KQQ, KQQQ, QQQ and QQ. Five apparent resistivity sections and eight isoresistivity contour maps were drawn. Quantitative interpretation was carried out using five geoelectrical sections which were drawn along the selected profiles. Number of the underlying layers, depths, thicknesses and depth of ground water table were determined for each VES point along the investigated profiles. Also, decreasing of the apparent resistivity values with depth was noticed especially at the groundwater bearing intervals. This is because of the increasing of salinity in ground water at these intervals especially at the mid-way of all considered profiles. The rise of saline water belong to the lower part of the Dibddiba aquifer towards the brackish or fresh water existed in the upper profile due to the unprogramm able pumping processes which may cause mixture between them and make the resultant water more saline. Large reduction in the apparent resistivity values was also observed at the eastern parts of the study area near Khor Al-Zubair boundaries which indicate high electrical conductivity values. This is led to the increasing of saline water that probably comes from the sea. This fact is certainly approved by the interpretation of the is oresistivity contour map plotted for the upper part of aquifer and by comparing hydrochemical analysis for ten wells with the above result.